Recognition of N-Glycolylneuraminic Acid Linked to Galactose by the α2,3 Linkage Is Associated with Intestinal Replication of Influenza A Virus in Ducks - Ito, Toshihiro (American Society for Microbiology, 2000)
The hemagglutinin (HA) of H3 human influenza viruses does not support viral replication in duck intestine despite its avian origin. A Leu-to-Gln mutation at position 226 and a Ser-to-Gly mutation at position 228 in the HA of human A/Udorn/307/72 (H3N2) permit a reassortant virus [human Udorn HA, with all other genes from A/mallard/New York/6750/78 (H2N2)] to replicate in ducks. To understand the molecular basis of this change in host range restriction, we investigated the receptor specificity of duck influenza viruses as well as of human-duck virus reassortants. The results indicate that the recognition of a glycoconjugate moiety possessing N-glycolneuramic acid (NeuGc) linked to galactose by the α2,3 linkage (NeuGcα2,3Gal) is associated with viral replication in duck intestine. Immunofluorescence assays with NeuGcα2,3Gal-specific antiserum detected this moiety primarily on the crypt epithelial cells of duck colon. Such recognition, together with biochemical evidence of NeuGc in crypt cells, correlated exactly with the ability of the virus to replicate in duck colon. These results suggest that recognition of the NeuGcα2,3-Gal moiety plays an important role in the enterotropism of avian influenza viruses.